Pelaksanaan Promosi pada UMKM Es Teler Monster - Kamelia Agnesta; Sudarijati Sudarijati (MANAJEMEN, 2026)
Competition in the culinary sector has encouraged micro, small, and medium enterprises (MSMEs) to implement effective promotional strategies to increase brand awareness and sales. However, in practice, many MSMEs still do not manage their promotional activities optimally. This study aims to analyze the effectiveness of promotional activities of Es Teler Monster MSME in Megamendung District, Bogor Regency, in terms of promotional messages, media, and timing. This study employed a descriptive approach with data collected through observation, interviews, and surveys of 15 consumers. The results show that Es Teler Monster MSME has implemented various promotional activities, including advertising, sales promotion, personal selling, public relations, and direct marketing. However, these activities have not been carried out consistently and optimally, particularly in terms of media selection and promotional timing. The survey results indicate that 56% of respondents consider the promotions to be fairly effective, while 44% perceive them as ineffective. These findings highlight the need to improve consistency in promotional timing and optimize the use of promotional media to enhance attractiveness, reach, brand awareness, and sales. This study provides recommendations for MSME actors to develop structured promotional schedules and to utilize digital media more actively and creatively in order to enhance promotional effectiveness.